1999
DOI: 10.1016/s0305-750x(99)00096-0
|View full text |Cite
|
Sign up to set email alerts
|

Working Women in an Urban Setting: Traders, Vendors and Food Security in Accra

Abstract: Data collected from a 1997 household survey carried out in Accra, Ghana, are used to look at the crucial role that women play as income earners and in securing access to food in urban areas. One-third of the households surveyed are headed by women. For all households, women's labor force participation is high, with 75 percent of all households having at least one working woman. The high number of female-headed households and the large percent of working women in the sample provide a good backdrop for looking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(115 citation statements)
references
References 20 publications
(18 reference statements)
6
109
0
Order By: Relevance
“…Rented houses in Korea have been shown to be associated with lower housing stability, amenities, quality and per capita living space, reflective of the household's socio-economic status (44,45) . Unemployment status or paying monthly rent may lead to a cut food expenditures when there are limited resources (46)(47)(48) . Kirkpatrick and Tarasuk (46) found that among low-income households, households that paid rent or mortgages had lower food expenditures than those without housing payments.…”
Section: Discussionmentioning
confidence: 99%
“…Rented houses in Korea have been shown to be associated with lower housing stability, amenities, quality and per capita living space, reflective of the household's socio-economic status (44,45) . Unemployment status or paying monthly rent may lead to a cut food expenditures when there are limited resources (46)(47)(48) . Kirkpatrick and Tarasuk (46) found that among low-income households, households that paid rent or mortgages had lower food expenditures than those without housing payments.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Women also engage in other income-generating activities, mainly the preparation and sale of street foods including kenkey (a local staple food made from fermented maize dough) and petty trading. 30,31 Sampling Procedure To enable easy canvassing during census and survey enumeration, the Ghana Statistical Service has created small nationwide divisions called enumeration areas (EAs). 32 There were a total of 80 EAs in the three communities (48 in Usher Town, 24 in James Town, and 8 in Agbogbloshie) which make up the study area.…”
Section: Study Settingmentioning
confidence: 99%
“…In both urban and rural areas in sub-Saharan Africa, women are the main income earners in approximately one-third of households. 43 In rural areas in developing countries, the number of female-headed households is increasing as men migrate for employment. 44 Women are often responsible for non-income-generating work that is also critical to family well-being, such as gathering water and firewood, preparing food and tending to livestock.…”
Section: Service Availabilitymentioning
confidence: 99%